Elbow-hand robotic exoskeletons for active and passive rehabilitation on post-stroke patients: A bioengineering review - Cornejo, José (2024)
The clinical applications and benefits of the use of a Robotic Exoskeleton for Rehabilitation (RER) in the elbow and hand are described because a RER is a high-quality alternative capable of restoring compromised functions and neurorehabilitation at the same time in post-stroke patients. Passive rehabilitation (PR) is usually applied in the early stages of post-stroke recovery. The responsibility of assisting physical medicine and rehabilitation (PM&R) doctors and the patient with passive exercises is a robotic system (RS); while active rehabilitation (AR) is applied regularly in late stages, it is like PR and its implications but requires the strength and support of the person to perform the exercises voluntarily. The objective of the present study is to collect, synthesize, and report relevant scientific studies related to the implementation of exoskeleton systems for elbow-hand rehabilitation. Various scientific literature on the topic was reviewed in the main biomedical databases using the population, intervention, comparison, results, and context (PICOC) criteria. This study presents the potential and describes a comprehensive and updated vision of the consequences and improvements obtained with the use of the RER and its advances. In conclusion, the usefulness and importance of a RER in various applied clinical practices have found numerous advantages, such as a better evaluation of spasticity, neuromotor recuperation, promoting neuroplasticity, and much more, which is of global relevance since this study gives us a greater understanding of the potential of these new perspectives to improve the rehabilitation of compromised functions in post-stroke cases with the use of RER.